Insider reputation and selling decisions: the unwinding of venture capital investments during equity IPOs - Lin, Timothy H; Smith, Richard L (Journal of Corporate Finance, 1998)
Data on selling by venture capitalists during the IPOs of their portfolio companies are used to examine the relation between insider selling decisions and reputation. We hypothesize that, in deciding whether to sell, venture capitalists balance the costs of continued managerial/monitoring involvement against the adverse reaction to selling. Further, they facilitate unwinding of investment positions by developing reputations for not selling overpriced shares. Evidence on the timing of IPOs and selling decisions of venture capitalists confirms the importance of reputation as a determinant of the organization of the venture capital market and as a factor affecting insider selling decisions.